The Core Problem and Impact of Child Marriage in Wonosobo: Phenomenological Study - Junaedi, Mahfudz (JURNAL PENELITIAN, 2020)
This phenomenological study aims to analyse the root cause and impact of child marriage in Wonosobo. Social facts show that child marriage has multiple effects on children, including the right to access information and education, and girls’ reproductive health. Through a qualitative approach, this study generates the result: First, the demographics of Wonosobo as a poor area correlate with child marriage. The impact is severe and often leads to domestic violence, divorce, and the parenting style. Second, child marriage has the potential to violate the right to grow, the right to access educational information, and the right to reproductive health. Therefore, the process of socialization, education, and involvement of all stakeholders in Wonosobo are hugely needed. Even though the Wonosobo authorities have issued Regent Regulation Number 34 of 2019 concerning Strategies to tackle child marriage, it has not been effective in preventing the issue.